DISK MATCHING DEVICES FOR METHODS OF EXTERIOR LEVELLING OF CAR BODY PANELS - Gnatov, A.; Trunova, I.; Argun, Sch.; Гнатов, А. В.; Трунова, І. С.; Аргун, Щ. В.; Гнатов, А. В.; Трунова, И. С.; Аргун, Щ. В. (Харьковский национальный автомобильно-дорожный университет, 2016)
The basic equipment of the given methods consists of the power source, the levelling tool and the matching device for exterior levelling methods of car body panels is presented in the paper. Using the obtained analytical expressions, the numerical estimations of the basic characteristics of the considered matching device have been plotted. The schematic solution as to technical realization of the disc matching device is proposed. The experimental approbation of the elaborated tool of the exterior magnetic and pulse levelling has been carried out.
УЗГОДЖУВАЛЬНІ ПРИСТРОЇ ДИСКОВОГО ТИПУ ДЛЯ МЕТОДІВ ЗОВНІШНЬОГО РИХТУВАННЯ КУЗОВНИХ ПАНЕЛЕЙ АВТОМОБІЛІВ
СОГЛАСУЮЩИЕ УСТРОЙСТВА ДИСКОВОГО ТИПА ДЛЯ МЕТОДОВ ВНЕШНЕЙ РИХТОВКИ КУЗОВНЫХ ПАНЕЛЕЙ АВТОМОБИЛЕЙ
Keywords: straightening; removing dents; body repair; matching device; рихтування; видалення вм’ятин; кузовний ремонт; узгоджувальний пристрій; рихтовка; удаление вмятин; кузовной ремонт; согласующее устройство; 621.318.4